Dynamical constraints on the long-term co-orbital State of (469219) Kamoʻoalewa - Gregory M. Davis; Jonathan Horner (Icarus, 2026)

Invasive barred owls select old-forest structure: Functional habitat loss for spotted owls and a threat to old-forest fauna - Vitek Jirinec; Mourad W. Gabriel; J. Mark Higley; Raymond J. Davis; Jonathan E. Tenberge; Christina P. Varian; Daniel F. Hofstadter; M. Zachariah Peery; Julianna M.A. Jenkins; Alan B. Franklin; Greta M. Wengert (Biological Conservation, 2026)

Bacillus subtilis endospore integrity and viability on simulated Martian regolith in rotational UVC radiation exposures - Gregory M Davis; Jonathan Horner; Andrew R Greenhill; Stephen C Marsden; Bradley D Carter (Life Sciences in Space Research, 2026)

A sea-to-soil solution for the green tides threatening shellfish aquaculture: conceptual model and lessons learned from a pilot project - Sarah M. Collier; Emily Buckner; Nicole J. Capizzi; Meg Chadsey; Douglas P. Collins; Jonathan P. Davis; Erick Dowell; Alan Ismach; Brittany G. Johnson; Sergey Rabotyagov; Rob Smith; Katie R. Webb; et al. (Journal of Environmental Management, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

When energy transitions drive polarization: Narratives of green energy and mitigation strategies by proponents and opponents of geothermal energy developments in Indonesia - Jonathan Davis Smith; Martha Hesty Susilowati; Samsul Maarif; Eko Cahyono (Energy Policy, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Environmental Life Cycle Assessment and Techno-Economic Analysis of Textile Waste Valorization via Modular Bioenergy with Carbon Capture, Utilization, and Storage - Jonathan Morizet-Davis; Yaojing Qiu; June Khongpatimakorn; Jesse Daystar; Kai Lan; Sunkyu Park; William Joe Sagues; Richard A. Venditti (BioEnergy Research, 2025)
Annually, over 92 million metric tonnes (Mt) of textile waste are produced globally, with 17 Mt discarded in the US alone. Textile waste is typically comprised of approximately 50% biomass-derived cellulosic fiber and 50% fossil carbon-derived synthetic fiber, with the biogenic portion representing a global CO 2 removal capacity estimated at 75 Mt CO 2 (14 Mt CO 2 in the US alone). Bioenergy with carbon capture and storage (BECCS) offers a promising solution for permanently removing atmospheric CO 2 by converting biomass into energy while capturing and storing the resulting carbon emissions. Despite its potential, textile waste remains an underutilized feedstock in BECCS research and deployment. This study evaluates the techno-economic feasibility and environmental performance of small-scale modular BECCS systems that process textile waste to produce electricity and achieve net-negative emissions. Four waste-to-energy scenarios were modeled using 100% cotton or a 50/50 cotton–polyethylene terephthalate (PET) blend, with and without carbon capture. In 2018, the US EPA reported that 66% of discarded textiles were landfilled. As a result, a fifth landfilling end-of-life scenario was introduced to compare valorization scenarios to a baseline scenario. Life cycle assessment (LCA) and techno-economic analysis (TEA) are applied to quantify levelized cost of electricity (LCOE) and CO 2 removal. For 100% cotton waste, the removal cost was 329 USD per metric ton (t) CO 2 e, significantly lower than 777 USD per t-CO 2 e for 50/50 cotton-PET. The carbon removal efficiencies of 100% cotton and 50/50 cotton-PET textile waste materials were 91% and 59%, respectively. The lowest LCOE was observed for a 50/50 cotton-PET mixture with CCS at 0.17 USD/kWh, due to the relatively high energy density of the feedstock. In contrast, 100% cotton with CCS had the highest LCOE at 0.29 USD/kWh due to the lower feedstock energy density, higher capital expenditure (CAPEX), and reduced CO 2 sales, due to the lower carbon content in cotton compared to PET. In addition, the LCOE for the 50/50 cotton-PET without CCS was 0.18 USD/kWh and the LCOE for the 100% cotton without CCS was 0.24 USD/kWh. The LCA with CCS showed that direct and indirect emissions lead to high acidification potential due to ammonia release via monoethanolamine (MEA) degradation, compared to electricity production without CCS. Additionally, the production of MEA itself exhibited high ecotoxicity potential compared to other process inputs such as NaOH and activated carbon. Overall, this study demonstrated textile waste’s potential as a viable alternative for producing bioenergy and waste-derived energy. In terms of overall environmental impact, all four valorization scenarios significantly outperformed landfilling.

Differential performance of diploid, mated triploid, and induced triploid Pacific oysters under varied environmental conditions: Insights into impacts of temperature, dissolved oxygen, and pCO2 - Craig Roger Norrie; D. Shallin Busch; Jonathan Davis; Paul McElhany; Jacqueline L. Padilla Gamiño (Aquaculture, 2025)

Sustainable production of xylo-oligosaccharides: A comparative environmental life cycle and techno-economic analysis - Jonathan Morizet-Davis; Song Wang; Hoyong Kim; Choonghyun Ham; Kai Lan; Richard Venditti; Sunkyu Park (Bioresource Technology Reports, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Soil health and ecological resilience of no-till, organic, and mixed-crop livestock systems in eastern Washington State - Alexandra.G. Davis; Lynne Carpenter-Boggs; Katherine L. Smith; Jonathan M. Wachter; Garett Heineck; David R. Huggins; John P. Reganold (Agriculture, Ecosystems & Environment, 2025)

Intensifying Fire Season Aridity Portends Ongoing Expansion of Severe Wildfire in Western US Forests - Sean A. Parks; Jonathan D. Coop; Kimberley T. Davis (Global Change Biology, 2025)
Area burned by wildfire has increased in western US forests and elsewhere over recent decades coincident with warmer and drier fire seasons. However, high–severity fire —fire that kills all or most trees—is arguably a more important metric of fire activity given its destabilizing influence on forest ecosystems and direct and indirect impacts to human communities. Here, we quantified area burned and area burned severely in western US forests from 1985 to 2022 and evaluated trends through time. We also assessed key relationships between area burned, extent and proportion burned severely, and fire season climate aridity. Lastly, using the strong relationships between fire season aridity and both area burned and area burned severely, we predicted future fire activity under ongoing warming. While annual area burned increased 10‐fold over our study period, area burned severely increased 15‐fold. Disproportionate increases in severe fire occurred across a wide range of forest types from 1985 to 2022. Importantly, we found that the proportion of area burned severely increased with fire extent at the scale of individual fires and total annual area burned. The relationships between fire season aridity and fire were strong, and our models predicted further increases in fire activity, leading to 2.9‐ and 4‐fold increases in area burned and area burned severely, respectively, under mid‐21st century climate. Without a substantial expansion of management activities that effectively reduce fire severity (e.g., thinning of understory and fire‐intolerant trees combined with prescribed fire), wildfires will increasingly drive forest loss and degrade ecosystem services including carbon storage, biodiversity conservation, and water yield, with major impacts to human communities.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Predictable patterns within the kelp forest can indirectly create temporary refugia from ocean acidification - Nina Bednaršek; Greg Pelletier; Marcus W. Beck; Richard A. Feely; Zach Siegrist; Dale Kiefer; Jonathan Davis; Betsy Peabody (Science of The Total Environment, 2024)

Review of per- and poly-fluoroalkyl treatment in combustion-based thermal waste systems in the United States - Keith Weitz; Debra Kantner; Andrew Kessler; Haley Key; Judd Larson; Wanda Bodnar; Sameer Parvathikar; Lynn Davis; Nicole Robey; Philip Taylor; Florentino De la Cruz; Thabet Tolaymat; et al. (Science of The Total Environment, 2024)

Association between prenatal exposure to indoor residual spraying insecticides and infection rates among South African children participating in the Venda Health Examination of Mothers, Babies and their Environment (VHEMBE) - Brooklyn Davis; Brenda Eskenazi; Riana Bornman; Muvhulawa Obida; Jonathan Chevrier (Science of The Total Environment, 2024)

How social movements use religious creativity to address environmental crises in Indonesian local communities - Jonathan Davis Smith; Ronald Adam; Samsul Maarif (Global Environmental Change, 2024)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Effect of Active Pharmaceutical Ingredient, Lipid Composition, and Thermal Processing on the Physical Stability of Local Anesthetic-loaded Lipid Microparticles - Sierra Erickson; Jonathan Vizmeg; Jack Shuckra; Susan Wojtalewicz; Andrew Cleveland; Jordan Davis; Michael Beeman; Stefan Niederauer; Himanshu Sant; Jayant Agarwal; Caleb Lade; Brett Davis (Journal of Pharmaceutical Innovation, 2023)

Stabilisation of PFAS in soils: Long-term effectiveness of carbon-based soil amendments - Divina A. Navarro; Shervin Kabiri; Jonathan Ho; Karl C. Bowles; Greg Davis; Mike J. McLaughlin; Rai S. Kookana (Environmental Pollution, 2023)

Evaluating how occupational exposure to organophosphates and pyrethroids impacts ADHD severity in Egyptian male adolescents - Hana-May Eadeh; Jonathan Davis; Ahmed A. Ismail; Gaafar M. Abdel Rasoul; Olfat M. Hendy; James R. Olson; Matthew R. Bonner; Diane S. Rohlman (NeuroToxicology, 2023)

SOD1-Related Cerebellar Ataxia and Motor Neuron Disease: Cp Variant as Functional Modifier? - Luca Marsili; Jennie L. Davis; Alberto J. Espay; Jonathan Gilthorpe; Chloe Williams; Marcelo A. Kauffman; Aleksey Porollo (The Cerebellum, 2023)

Food and Physical Activity Environment in the US-Affiliated Pacific Region: The Children's Healthy Living Program - Ashley B. Yamanaka; Sabine Strasburger; Courtney Chow; Jean Butel; Lynne Wilkens; James D. Davis; Jonathan Deenik; Leslie Shallcross; Rachel Novotny (Journal of Nutrition Education and Behavior, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Cancer microenvironment and genomics: evolution in process - Stanley P. Leong; Isaac P. Witz; Orit Sagi-Assif; Sivan Izraely; Jonathan Sleeman; Brian Piening; Bernard A. Fox; Carlo B. Bifulco; Rachel Martini; Lisa Newman; Melissa Davis; Lauren M. Sanders; et al. (Clinical & Experimental Metastasis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Carolina critters: a collection of camera‐trap data from wildlife surveys across North Carolina - Monica Lasky; Arielle W. Parsons; Stephanie G. Schuttler; George Hess; Ron Sutherland; Liz Kalies; Staci Clark; Colleen Olfenbuttel; Jessie Matthews; James S. Clark; Jordan Siminitz; George Davis; et al. (Ecology, 2021)
Camera trap surveys are useful to understand animal species population trends, distribution, habitat preference, behavior, community dynamics, periods of activity, and species associations with environmental conditions. This information is ecologically important, because many species play important roles in local ecosystems as predators, herbivores, seed dispersers, and disease vectors. Additionally, many of the larger wildlife species detected by camera traps are economically important through hunting, trapping, or ecotourism. Here we present a data set of camera‐trap surveys from 6,043 locations across all 100 counties of North Carolina, USA from 2009 to 2019. These data come from 26 survey initiatives and contain 215,108 records of 36 mammal species and three species of terrestrial birds. This large data set increases the geographical distribution data for these 39 mammal and bird species by >500% over what is available for North Carolina in the Global Biodiversity Information Facility (GBIF). These data can be used to conduct inquiries about species, populations, communities, or ecosystems, and to produce useful information on wildlife behavior, distribution, and interactions. There are no copyright restrictions. Please cite this paper when using the data for publication.

Phenological sensitivity to temperature mediates herbivory - Emily K. Meineke; Charles C. Davis; T. Jonathan Davies (Global Change Biology, 2021)
Species interactions drive ecosystem processes and are a major focus of global change research. Among the most consequential interactions expected to shift with climate change are those between insect herbivores and plants, both of which are highly sensitive to temperature. Insect herbivores and their host plants display varying levels of synchrony that could be disrupted or enhanced by climate change, yet empirical data on changes in synchrony are lacking. Using evidence of herbivory on herbarium specimens collected from the northeastern United States and France from 1900 to 2015, we provide evidence that plant species with temperature‐sensitive phenologies experience higher levels of insect damage in warmer years, while less temperature‐sensitive, co‐occurring species do not. While herbivory might be mediated by interactions between warming and phenology through multiple pathways, we suggest that warming might lengthen growing seasons for phenologically sensitive plant species, exposing their leaves to herbivores for longer periods of time in warm years. We propose that elevated herbivory in warm years may represent a previously underappreciated cost to phenological tracking of climate change over longer timescales.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Farm production diversity and its association with dietary diversity in Kenya - Davis Muthini; Jonathan Nzuma; Rose Nyikal (Food Security, 2020)

Assessment of Gene Expression Biomarkers in the Chilean Pencil Catfish, Trichomycterus areolatus, from the Choapa River Basin, Coquimbo Chile - Jonathan M. Ali; Angela Montecinos; Thomas T. Schulze; Luke G. Allmon; Alex T. Kallenbach; Gabrielle F. Watson; Paul H. Davis; Daniel D. Snow; Angéline Bertin; Nicolas Gouin; Alan S. Kolok (Archives of Environmental Contamination and Toxicology, 2020)

Paired involvement of human-specific Olduvai domains and NOTCH2NL genes in human brain evolution - Ian T. Fiddes; Alex A. Pollen; Jonathan M. Davis; James M. Sikela (Human Genetics, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Biogeographic patterns of communities across diverse marine ecosystems in southern California - Jeremy T. Claisse; Carol A. Blanchette; Jenifer E. Dugan; Jonathan P. Williams; Jan Freiwald; Daniel J. Pondella; Nicholas K. Schooler; David M. Hubbard; Kathryn Davis; Laurel A. Zahn; Chelsea M. Williams; Jennifer E. Caselle (Marine Ecology, 2018)
Integrating results from monitoring efforts conducted across diverse marine ecosystems provides opportunities to reveal novel biogeographic patterns at larger spatial scales and among multiple taxonomic groups. We investigated large‐scale patterns of community similarity across major taxonomic groups (invertebrates, fishes or algae) from a range of marine ecosystems (rocky intertidal, sandy intertidal, kelp forest, shallow and deep soft‐bottom subtidal) in southern California. Because monitoring sites and methods varied among programs, site data were averaged over larger geographic regions to facilitate comparisons. For the majority of individual community types, locations that were geographically near or environmentally similar to one another tended to have more similar communities. However, our analysis found that this pattern of within community type similarity did not result in all pairs of these community types exhibiting high levels of cross‐community congruence. Rocky intertidal algae communities had high levels of congruence with the spatial patterns observed for almost all of the other (fish or invertebrate) community types. This was not surprising given algal distributions are known to be highly influenced by bottom‐up factors and they are important as food and habitat for marine fishes and invertebrates. However, relatively few pairwise comparisons of the spatial patterns between a fish community and an invertebrate community yielded significant correlations. These community types are generally comprised of assemblages of higher trophic level species, and additional ecological and anthropogenic factors may have altered their spatial patterns of community similarity. In most cases pairs of invertebrate community types and pairs of fish community types exhibited similar spatial patterns, although there were some notable exceptions. These findings have important implications for the design and interpretation of results of long‐term monitoring programs.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Loss of the nutrient sensor TAS1R3 leads to reduced bone resorption - Michael S. Eaton; Nicholas Weinstein; Jordan B. Newby; Maggie M. Plattes; Hanna E. Foster; Jon W. Arthur; Taylor D. Ward; Stephen R. Shively; Ryann Shor; Justin Nathan; Hannah M. Davis; Lilian I. Plotkin; et al. (Journal of Physiology and Biochemistry, 2018)

Range position and climate sensitivity: The structure of among‐population demographic responses to climatic variation - Staci M. Amburgey; David A. W. Miller; Evan H. Campbell Grant; Tracy A. G. Rittenhouse; Michael F. Benard; Jonathan L. Richardson; Mark C. Urban; Ward Hughson; Adrianne B. Brand; Christopher J. Davis; Carmen R. Hardin; Peter W. C. Paton; et al. (Global Change Biology, 2018)
Species’ distributions will respond to climate change based on the relationship between local demographic processes and climate and how this relationship varies based on range position. A rarely tested demographic prediction is that populations at the extremes of a species’ climate envelope (e.g., populations in areas with the highest mean annual temperature) will be most sensitive to local shifts in climate (i.e., warming). We tested this prediction using a dynamic species distribution model linking demographic rates to variation in temperature and precipitation for wood frogs ( Lithobates sylvaticus ) in North America. Using long‐term monitoring data from 746 populations in 27 study areas, we determined how climatic variation affected population growth rates and how these relationships varied with respect to long‐term climate. Some models supported the predicted pattern, with negative effects of extreme summer temperatures in hotter areas and positive effects on recruitment for summer water availability in drier areas. We also found evidence of interacting temperature and precipitation influencing population size, such as extreme heat having less of a negative effect in wetter areas. Other results were contrary to predictions, such as positive effects of summer water availability in wetter parts of the range and positive responses to winter warming especially in milder areas. In general, we found wood frogs were more sensitive to changes in temperature or temperature interacting with precipitation than to changes in precipitation alone. Our results suggest that sensitivity to changes in climate cannot be predicted simply by knowing locations within the species’ climate envelope. Many climate processes did not affect population growth rates in the predicted direction based on range position. Processes such as species‐interactions, local adaptation, and interactions with the physical landscape likely affect the responses we observed. Our work highlights the need to measure demographic responses to changing climate.

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

Evidence of Ostrea lurida Carpenter, 1864, population structure in Puget Sound, WA, USA - Jake E. Heare; Brady Blake; Jonathan P. Davis; Brent Vadopalas; Steven B. Roberts (Marine Ecology, 2017)
Species traits that carry adaptive advantages such as reproductive timing and stress resilience may differ among populations. Knowledge and consideration of these traits should, therefore, be integrated into conservation efforts that include long‐term persistence of species. To test for adaptive differences between Olympia oyster, Ostrea lurida , populations a reciprocal transplant experiment was carried out monitoring survival, growth and reproduction using three established populations of O. lurida within Puget Sound, WA, USA . Performance differed for each population. Ostrea lurida from Dabob Bay had the highest survival at all sites but the lowest reproductive activity and growth. Oysters from Oyster Bay demonstrated the greatest proportion of brooding females at a majority of sites with moderate growth and survival. Together these data suggest the existence of O. lurida population structure within Puget Sound and provide information on how broodstock should be selected for restoration purposes.

Riverscape genetic structure of a threatened and dispersal limited freshwater species, the Rocky Mountain Sculpin (Cottus sp.) - Jonathan L. W. Ruppert; Patrick M. A. James; Eric B. Taylor; Tyana Rudolfsen; Marie Veillard; Corey S. Davis; Doug Watkinson; Mark S. Poesch (Conservation Genetics, 2017)

Antihypertensive medication use and risk of renal cell carcinoma - Joanne S. Colt; Jonathan N. Hofmann; Kendra Schwartz; Wong-Ho Chow; Barry I. Graubard; Faith Davis; Julie Ruterbusch; Sonja Berndt; Mark P. Purdue (Cancer Causes & Control, 2017)

Connectivity-based parcellation of the human frontal polar cortex - Massieh Moayedi; Tim V. Salomons; Katharine A. M. Dunlop; Jonathan Downar; Karen D. Davis (Brain Structure and Function, 2015)

Field Evaluation of Transgenic Switchgrass Plants Overexpressing PvMYB4 for Reduced Biomass Recalcitrance - Holly L. Baxter; Charleson R. Poovaiah; Kelsey L. Yee; Mitra Mazarei; Miguel Rodriguez; Olivia A. Thompson; Hui Shen; Geoffrey B. Turner; Stephen R. Decker; Robert W. Sykes; Fang Chen; Mark F. Davis; et al. (BioEnergy Research, 2015)

A multiproxy (micro‐XRF, pollen, chironomid and stable isotope) lake sediment record for the Lateglacial to Holocene transition from Thomastown Bog, Ireland - JONATHAN N. TURNER; NAOMI HOLMES; STEPHEN R. DAVIS; MELANIE J. LENG; CATHERINE LANGDON; ROBERT G. SCAIFE (Journal of Quaternary Science, 2015)
A multiproxy Lateglacial environmental record is presented for a ca. 3.5‐m lacustrine sequence retrieved from a small basin (ca. 2 km 2 ) at Thomastown Bog in County Meath, Ireland. Sediment chemistry, pollen, chironomid and stable isotope data provide a detailed picture of catchment and lake system changes from the end of the last glacial (GS‐2a) to the early Holocene that correspond closely to existing local and regional models of climate change. Concomitant adjustments in independent proxy records are matched to the NGRIP oxygen isotope curve giving 12 event‐episodes ranging from major climatic shifts to lower amplitude, centennial‐ to sub‐centennial‐scale adjustments, including a previously unreported regressive period of landscape instability during the north‐west European ‘Rammelbeek Phase’. The study emphasizes the potential of palaeoenvironmental reconstruction from sediment chemistry where the sediment mixing system reflects autochthonous versus allochthonous inputs. The investigation also indicates problems of interpreting isotope data derived from bulk marl due to possible lag effects controlling the delivery of soil and groundwater and multiple sources of HCO 3– (aq.). These research findings have implications for core site selection and for studies attempting to use stable isotopes for correlation purposes.

Tri-modal regulation of cardiac muscle relaxation; intracellular calcium decline, thin filament deactivation, and cross-bridge cycling kinetics - Brandon J. Biesiadecki; Jonathan P. Davis; Mark T. Ziolo; Paul M. L. Janssen (Biophysical Reviews, 2014)

Exome sequencing and arrayCGH detection of gene sequence and copy number variation between ILS and ISS mouse strains - Laura Dumas; C. Michael Dickens; Nathan Anderson; Jonathan Davis; Beth Bennett; Richard A. Radcliffe; James M. Sikela (Mammalian Genome, 2014)

Low genetic variation in cold tolerance linked to species distributions in butterflies - Jonathan M. P. Davis; Belinda van Heerwaarden; Carla M. Sgrò; Jennifer A. Donald; Darrell J. Kemp (Evolutionary Ecology, 2014)

Impact of water on CO2 capture by amino acid ionic liquids - Jonathan L. McDonald; Richard E. Sykora; Paul Hixon; Arsalan Mirjafari; James H. Davis (Environmental Chemistry Letters, 2014)

Two spatial scales in a bleaching event: Corals from the mildest and the most extreme thermal environments escape mortality - Jesús Pineda; Victoria Starczak; Ann Tarrant; Jonathan Blythe; Kristen Davis; Tom Farrar; Michael Berumen; José C. B. da Silva (Limnology and Oceanography, 2013)
In summer 2010, a bleaching event decimated the abundant reef flat coral Stylophora pistillata in some areas of the central Red Sea, where a series of coral reefs 100–300 m wide by several kilometers long extends from the coastline to about 20 km offshore. Mortality of corals along the exposed and protected sides of inner (inshore) and mid and outer (offshore) reefs and in situ and satellite sea surface temperatures (SSTs) revealed that the variability in the mortality event corresponded to two spatial scales of temperature variability: 300 m across the reef flat and 20 km across a series of reefs. However, the relationship between coral mortality and habitat thermal severity was opposite at the two scales. SSTs in summer 2010 were similar or increased modestly (0.5°C) in the outer and mid reefs relative to 2009. In the inner reef, 2010 temperatures were 1.4°C above the 2009 seasonal maximum for several weeks. We detected little or no coral mortality in mid and outer reefs. In the inner reef, mortality depended on exposure. Within the inner reef, mortality was modest on the protected (shoreward) side, the most severe thermal environment, with highest overall mean and maximum temperatures. In contrast, acute mortality was observed in the exposed (seaward) side, where temperature fluctuations and upper water temperature values were relatively less extreme. Refuges to thermally induced coral bleaching may include sites where extreme, high‐frequency thermal variability may select for coral holobionts preadapted to, and physiologically condition corals to withstand, regional increases in water temperature.

Molecular systematics of the genus Sonora (Squamata: Colubridae) in central and western Mexico - Christian L. Cox; Alison R. Davis Rabosky; Jacobo Reyes-Velasco; Paulino Ponce-Campos; Eric N. Smith; Oscar Flores-Villela; Jonathan A. Campbell (Systematics and Biodiversity, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

A Biogeochemical View of Estuarine Eutrophication: Seasonal and Spatial Trends and Correlations in the Delaware Estuary - Jonathan H. Sharp; Kohei Yoshiyama; Alexander E. Parker; Matthew C. Schwartz; Susan E. Curless; Allison Y. Beauregard; Justin E. Ossolinski; Allen R. Davis (Estuaries and Coasts, 2009)

Genomic regions influencing gene expression of the HMW glutenins in wheat - Eric W. Storlie; Robert J. Ihry; Leslie M. Baehr; Karissa A. Tieszen; Jonathan H. Engbers; Jordan M. Anderson-Daniels; Elizabeth M. Davis; Anne G. Gilbertson; Niels R. Harden; Kristina A. Harris; Amanda J. Johnson; Amy M. Kerkvleit; et al. (Theoretical and Applied Genetics, 2009)

Dissociation of force decline from calcium decline by preload in isolated rabbit myocardium - Michelle M. Monasky; Kenneth D. Varian; Jonathan P. Davis; Paul M. L. Janssen (Pflügers Archiv - European Journal of Physiology, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

Modification of the Copolymers Poloxamer 407 and Poloxamine 908 can Affect the Physical and Biological Properties of Surface Modified Nanospheres - Jonathan C. Neal; S. Stolnik; M. C. Garnett; Stanley S. Davis; Lisbeth Illum (Pharmaceutical Research, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

SimRoot: Modelling and visualization of root systems - Jonathan P. Lynch; Kai L. Nielsen; Robert D. Davis; Andrei G. Jablokow (Plant and Soil, 1997)